2020
DOI: 10.1080/10298436.2020.1778694
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of hot mix asphalt with recycled concrete aggregates for road pavements construction

Abstract: In this study a comparative life cycle assessment (LCA) was conducted according to a 'cradle-to-laid' approach to evaluate the potential environmental impacts related to the use of recycled concrete aggregates (RCAs) as a partial replacement of coarse natural aggregates in the production of Hot Mix Asphalt (HMA). Specifically, three percentages of RCA replacements were analyzed: 15, 30 and 45%. Primary data collected mainly through surveys performed in Colombian contractors from the region of Barranquila were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…RCA is a material composed of virgin aggregates covered by a layer of cement mortar [8], these wastes are part of the composition of Construction and Demolition (C&D) waste. Bonded cement mortar is related to different undesirable characteristics of RCA behavior, such as higher absorption, lower durability, and lower mechanical behavior; compared to natural aggregates [3], [10]. However, as a replacement of the Natural Aggregates (NA) in road structures in certain percentages, RCA have shown a relatively good performance [10].…”
Section: Introductionmentioning
confidence: 99%
“…RCA is a material composed of virgin aggregates covered by a layer of cement mortar [8], these wastes are part of the composition of Construction and Demolition (C&D) waste. Bonded cement mortar is related to different undesirable characteristics of RCA behavior, such as higher absorption, lower durability, and lower mechanical behavior; compared to natural aggregates [3], [10]. However, as a replacement of the Natural Aggregates (NA) in road structures in certain percentages, RCA have shown a relatively good performance [10].…”
Section: Introductionmentioning
confidence: 99%
“…The findings showed that the environmental impacts and costs decreased by 96.5% and 97.3%, respectively, and the quality level increased by 125.1% compared to the basic method. Other researchers, such as Santos et al [23] and Vega et al [24], also addressed the issue of the environmental impact assessment in hot asphalt and concrete pavement projects.…”
Section: Introductionmentioning
confidence: 99%
“…It showed that the global warming potential of NMAM was 7.45 × 10 3 kg CO 2 -equivalent per unit of function as opposed to 7.42 × 10 3 kg CO 2 -equivalent per traditional asphalt mixture unit of function. As reported by L. Vega A. et al [ 18 ], the possible environmental effects of the usage of recycled concrete aggregate (RCA) in the manufacture of HMA as a fractional exchange of natural coarse aggregates were evaluated. It is obvious that mixtures containing 30% and 15% of RCA may be regarded as eco-friendly choices to the traditional mixture (i.e., without RCA content), as those two contents enabled decreases in every effect category rating.…”
Section: Introductionmentioning
confidence: 99%